PENGEMBANGAN BAHAN AJAR TENTANG SEKOLAH RAMAH ANAK PADA MATA KULIAH MANAJEMEN BERBASIS SEKOLAH - Hernawati Damanik; Sondang Purnamasari Pakpahan (Universitas Negeri Medan, 2018)
ABSTRACT This study aimed to find out the tutorial perception of students, teacher and headmaster of elementary school, about the management based on school which is familiar with children and children’s rights, evaluation, learning material and tutorial process on learning management based on school (MBS), arranging the material concept and instructional model in open university (UT). This study was conducted in elementary school located in Sei Balai sub-district, Batubara regency, the province of North Sumatera. It observed the students of PGSD, lecturer, teachers and headmaster. The steps used in conducting this resign to the teaching material UT is Dick and Carrey model. The result of this research is tutorial’s perception, university students, teachers and the headmaster to the modul MBS UT : (a) Good enough but it is unuseful due to the school otonomy is not specificly implemented to state elementary school, (b) MBS material according to students is needed to be added with school management related to HAM and children protection, (c) Most of the teachers said that they need to know about school management which are familiar to children, (d) a suitable tutorial system in an opened learning university (UT) that its instructional process management school based lesson tends to have eight times meeting tutorial, and there is no assignment given thus the students do observation about practising MBS at school, (e) Material learning MBS in opened learning university (UT) needs to be modified with the six moduls, but it is more than 15 learning activities. Then it has 18 learning activities by adding the learning material about school which are familiar to the children, children’s rights and children management.Keywords : material learning, school familiar to the children, management school based.